A tale of two genera: the revival of Hoplodoris (Nudibranchia: Discodorididae) with the description of new species of Hoplodoris and Asteronotus - Donohoo, Samantha A.; Gosliner, Terrence M. (Zootaxa, 2020)
Nudibranchs in the family Discodorididae are generally medium (~30mm) to large (> 50mm) in size, sometimes cryptic, and are found in almost every marine ecosystem around the world. The diversity and systematics of the genera within Discodorididae are poorly understood and have led to numerous taxonomic changes. Hoplodoris Bergh, 1880 has recently been considered a synonym of Asteronotus Ehrenberg, 1831; however, morphological and molecular phylogenetic analyses reveal a distinct separation between these two genera. Here we provide a re-description of the type species Hoplodoris desmoparypha as well as descriptions of four undescribed species of Asteronotus and Hoplodoris. Bayesian inference and maximum likelihood analyses of two mitochondrial and two nuclear genes were used to evaluate the phylogenetic positions of the new species and clarify the relationships between Asteronotus and Hoplodoris to the rest of the Discodorididae. Based on our results, Hoplodoris is removed from synonymy with Asteronotus. Descriptions for Asteronotus markaensis sp. nov., and Asteronotus namuro sp. nov. from the Red Sea, as well as Hoplodoris balbon sp. nov. and Hoplodoris rosans sp. nov. from the western Pacific are provided.